PENGARUH INFLASI DAN SUKU BUNGA TERHADAP HARGA SAHAM PT BANK MNC INTERNASIONAL TBK PERIODE 2014-2018 - Fiki Priadi, Elfreda Aplonia Lau, dan Sunarto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study aims to determine and analyze the effect of inflation and interestrates on stock prices partially or simultaneously.The theoretical basis used in this research is especially about inflation,interest rates and stock prices.The analysis technique used in this research is multiple linear regression.Results of this study indicate that inflation has a significant positive effecton stock prices. Interest rates have a significant positive effect on stockprices. Inflation and interest rates have a simultaneusous significant positifeffect on stock prices.